"African Verbal Arts Online: Intermediality and 'Technauriture'" - (:unkn) unknown (My University, 2021)
In his classic work African Oral Literatures, Isidore Okpewho discloses a keen interest in contemporary dynamics of orality. This article on orality on the Internet is informed by Okpewho’s insights and hopes to contribute to the understanding of the “new life” of oral genres in the re-localisation of African diasporas on and offline.
Keywords: African Research